Isolation and Characterization of Natural Cellulose from Oxytenanthera abyssinica (Lowland Ethiopian Bamboo) Using Alkali Peroxide Bleaching Stages Followed by Aqueous Chlorite in Buffer Solution - Limenew Abate Worku; Rakesh Kumar Bachheti; Mesfin Getachew Tadesse (International Journal of Polymer Science)
Plants are the primary sources of cellulose. This paper is aimed at isolating cellulose from Oxytenanthera abyssinica via chemical treatments. The thermal behavior, functional group, chemical composition, crystallinity, and morphology of raw (ROA), dewaxed (DOA), alkali-treated (AOA), and bleached (BOA) fibers were examined. TGA, FTIR, DSC, DTA, XRD, and SEM were used for characterization techniques. The effects of chemical treatments were examined by determining the content of cellulose, hemicellulose, lignin, and ash. The cellulose content in the ROA improved from 49.26±0.13 wt% to 86.01±0.02 wt% due to the removal of noncellulose components using waxing, alkali treatment, and bleaching with alkali peroxide bleaching stages followed by aqueous chlorite in buffer solution. The highest content of cellulose and holocellulose was exhibited in the BOA samples with a yield of 86.01±0.02 wt% and 97.61±0.17 wt%, respectively. ROA had greater hemicellulose (21.31±0.15 wt%), lignin (20.63±0.12 wt%), and ash content (3.30±0.11 wt%) in comparison to AOA and BOA. The XRD data showed a change in crystallinity after each treatment. Because of the high amount of crystalline cellulose, the XRD results revealed that BOA has a higher crystallinity index (CrI) (59.89%) and peak intensity than AOA, DOA, and ROA. The strength of the FTIR peaks increased in the order of ROA, DOA, AOA, and BOA, indicating that pretreatment causes hemicellulose and lignin to be gradually removed from the Oxytenanthera abyssinica fiber. The TGA, DTG, DTA, and DSC data also confirmed that BOA has the highest thermal stability due to the high content of cellulose. The SEM analysis showed a morphological change in the surface due to chemical treatment. These results confirmed that through chemical pretreatment, a high amount of cellulose was produced from Oxytenanthera abyssinica. Even though Oxytenanthera abyssinica is commonly grown in Ethiopia, few studies have been done on it, and no works have been carried out to isolate and characterize cellulose from the plant. Thus, the findings in this work will encourage researchers to use Oxytenanthera abyssinica as a source of cellulose for various applications, including the manufacture of cellulose nanocrystals, polymer matrix biofilters, green biocomposite reinforcing agents, and hydrogel synthesis.